Proteomic analysis of the acquired enamel pellicle and saliva in patients with head and neck cancer to submitted radiotherapy - Ventura, Talita Mendes Oliveira (2021)
Salivary glands are affected during radiotherapy in the head and neck region, leading to reduction in salivary flow and changing saliva composition. In this thesis, comprising 6 articles, we evaluated changes in the proteomic profile of the acquired enamel pellicle (AEP) and saliva in patients with head and neck cancer (HNC) submitted to radiotherapy, to search for therapeutic strategies and prognosis biomarkers. In the first two articles the protocols for standardization of proteomic analysis of saliva and collection of AEP are described. In articles 3, 4 and 5, HNC patients had their AEP and saliva (unstimulated and stimulated saliva) collected before (BRT), during (2-5 weeks; DRT) and after (3-4 months; ART) radiotherapy. Saliva and AEP were also collected from healthy patients (control; C). Proteins were extracted and processed for label-free proteomics. Salivary flows were also evaluated. In total, 1,055 proteins were identified in the unstimulated saliva, among which 47 were common to all groups, while 86, 86, 286 and 395 were exclusively found in C, BRT, DRT and ART, respectively. Remarkably, alpha-enolase was increased 35-fold DRT compared with BRT, while proline-rich proteins (PRPs) were decreased. ART there was a 16-fold increase in scaffold attachment factor-B1 and a 3-fold decrease in alpha-enolase and cystatins. When compared with C, salivary proteins of BRT patients showed increases in cystatin-C, lysozyme C, histatin-1 and PRPs (article 3). Significant differences were observed between stimulated and unstimulated salivary flows for C and BRT (p>0.001), but not for DRT and ART. Proteins involved with apoptosis and antibacterial function were decreased in stimulated saliva in comparison to unstimulated saliva DRT and ART (article 4). In the AEP, statherin was increased more than 9-fold and hemoglobins were increased more than 5-fold DRT compared to BRT, while lactotransferrin, PRPs cystatins, neutrophil defensins and histatin-1 were decreased. ART, lactotransferrin and isoforms of histones were increased, while statherin and alpha-amylase were decreased. MOAP-1 was exclusively found ART compared to BRT. When compared to Control, AEP of patients BRT showed an increase in proteins related to the perception of bitter taste, mucin-7 and alpha-amylases, while cystatin-S was decreased (article 5). In article 6, we evaluated the protective effect AEP formed in vitro for different times on enamel, as well as its engineering with statherin peptide (StatpSpS), against initial erosion. AEP provided almost instant protection, with formation times as short as 1 min protecting the native enamel against erosion, and longer formation times did not improve the protection. StatpSpS by itself provided similar protection as the AEP. In conclusion, both HNC and radiotherapy remarkably alter the proteome of saliva and AEP. The unstimulated salivary flow is the best alternative to search for biomarkers. Monitoring alpha-enolase levels in unstimulated saliva DRT and MOAP-1 in AEP ART might be possible strategies to predict the efficacy of radiotherapy. Our results provide important information for designing more effective dental products for these patients and contribute for a better understanding of the progressive changes in salivary proteins induced by radiotherapy and the protective roles of the AEP proteins DRT.